Pengaruh Promosi dan Harga terhadap Keputusan Pembelian yang Berimplikasi pada Kepuasan Pelanggan: Studi pada Produk Gamis UMKM Shofy Collection dan Endomoda di Bandung - Sopiah, Yayah; Somadi, Somadi (ALSYS, 2025)
The gamis industry, as part of the Muslim fashion sector, has experienced rapid growth over the past decade but has faced significant pressure due to the pandemic and shifting consumer behavior. Amid increasing competition and declining revenue, business actors are required to develop effective promotional and pricing strategies to influence purchasing decisions and enhance customer satisfaction. This study aims to analyze the effects of promotion and price on purchasing decisions, as well as the effect of purchasing decisions on customer satisfaction for gamis products from two local MSMEs: Shofy Collection and Endomoda. A quantitative research method was employed using a survey approach, with 96 purposively selected respondents. Data were analyzed using SmartPLS version 4. The results show that promotion (β = 0.523) and price (β = 0.406) have a positive and significant influence on purchasing decisions, while purchasing decisions significantly affect customer satisfaction (β = 0.886). The research model demonstrates high predictive power, with R² values of 0.579 for purchasing decisions and 0.823 for customer satisfaction. These findings highlight the importance of optimizing digital promotional strategies, adaptively adjusting pricing, and enhancing post-purchase services as strategic efforts to build customer loyalty in the Muslim fashion market.